From awareness to action: Understanding urban community participation in tree planting initiatives - Prestisia Intan Nurcahyani Kusumaningtyas (Sustainable Urban Development and Environmental Impact Journal, 2025)
Background: Tree planting activities in urban areas are an important strategy to enhance the environmental quality for the communities living in those regions. Tree planting offers numerous benefits that can be experienced in daily life, which is why it is essential to raise awareness, particularly among urban communities, to engage in tree planting around their residential area. In addition to the benefits gained from tree planting, there are also potential drawbacks that can arise from planting trees in urban areas. This article aims to examine the awareness behaviour of tree planting and the barriers faced by urban communities in this regard. Methods: Through a literature review and a study of the perceptions of the community in Tangerang City, this research identifies the factors influencing individual decisions to engage in tree planting and measures the positive impacts generated by such initiatives. Findings: The primary motivations of residents for tree planting are to improve air quality, reduce temperatures, and simultaneously enhance the beauty and aesthetics of the surrounding environment. Additionally, participation in urban tree planting is often influenced by environmental awareness, community support, and government policies. Some of the benefits of tree planting include improved air quality, CO2 emission absorption from human activities, and the enhancement of green spaces that positively impact public health. Conclusions: This study concludes that increasing awareness of the benefits of tree planting, along with support from the government and communities, can encourage broader participation in these activities. Policy recommendations include promoting tree planting programs, providing incentives for participants, and strengthening cooperation among stakeholders, all of which are expected to achieve more optimal outcomes in urban environmental management. Novelty/Originality of this Article: This study offers a novel perspective by exploring the awareness behavior and barriers faced by urban communities in tree planting, particularly in Tangerang City, Indonesia. Unlike previous studies that primarily focus on environmental impacts, this research integrates social perceptions to provide a comprehensive understanding of community motivations and challenges.